Sudden weakness due to thyrotoxic periodic paralysis: a case report - Rizaldy Taslim Pinzon; Bulan Marchellia Wijaya; Edwin Timoti Japanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Thyrotoxic periodic paralysis (TPP) is a complication of hyperthyroidism. Lead to sudden hypokalemia and muscle weakness. In most cases, it is found mainly in young adult males of the Asian race. The paralysis is temporary and will return with potassium correction. There are very few cases reported in Indonesia regarding these cases of TPP. In our case, a 44-year old man complained of weakness that started later in the limbs but quickly improved. This case was diagnosed late at first, and uncorrected potassium levels led to recurrent paralysis. Laboratory test results showed severe hypokalemia (potassium level 1.81 mmol/L). The thyroxine level (T4) was 44.12 pmol/L and low serum thyroid-stimulating hormone (TSH) <0.0025 IU/mL.